De commune van Parijs - Schoeters, Robert; Bracke, Albert; De Weerdt, Frans (Antwerpen, 1968)
"Robert Schoeters; Albert Bracke, Frans De Weerdt; ... et al. Themanummer Mens en taak, jg. 11 nr. 4, 1968"